Monitoring of vital activities in fattening bulls as an innovative element of feedlots - Jeník, David; Falta, Daniel; Navrátil, Stanislav; Večeřa, Milan; Polák, Ondřej; Chládek, Gustav (Animal Welfare, Etológia és Tartástechnológia (AWETH), 2020)
Monitoring of vital activities of cattle is increasingly used for welfare assessment. The situation is relatively complex for growing cattle populations as the performance response is usually manifested in months and there is practically no routine opportunity to assess it rapidly. Therefore it is important to monitor vital activities and quantify their relationship with body weight gain during fattening. It can be assumed that the positive trends between the vital activity performance and welfare of the animals described in dairy cows can also be monitored in fattened bulls. There are several systems in precision livestock farming which can monitor the actual helath and activity levels of the animals. One of these is the SCR HR tag. The experiment was carried out on 14 bulls of the Czech Fleckvieh Simmental breed and lasted 84 days. We can conclude that there was a positive relationship between vital activities (eating and rumination) and daily weight gain of bulls between age 259 and 343. Activity „eating“ had an average value of 263.4 min (sx = ±46,2 min, Vx = 17.5%) while average „rumination“ lasted 508.6 min. The value of the correlation coefficients (r = 0.378 for „eating“ and r = 0.336 for „rumination“) together with the high variability especially in the „eating“ indicates the need for further experiments in this area.